Perbedaan Kadar LDL Dan HDL Pada Penderita Stroke Iskemik Baru Dengan Stroke Iskemik Rekuren Di Rsu Haji Medan Tahun 2015-2016 - Aribowo, Fadhilah Ramadhan; Andina, Meizly (Universitas Muhammadiyah Sumatera Utara, 2018)
Introduction: StrokeÂ refers to any sudden neurological disorder that occurs due to cessation of blood flow through the arterial supply system of the brain.Â The etiology obstructions are atherosclerosis. LDL is often associated with atherosclerosis. The increased of HDL levels may act as a protective factor against atherosclerosis, HDL <40 mg/dl is at risk for atherosclerotic plaque formation. The aim of this study was to compare LDL and HDL levels in stroke acute and recurrent. Methods: Secondary data obtained from RSU Haji Medan. Secondary data collected were data on LDL and HDL levels in patients with acute stroke and recurrent stroke by collecting medical records according to specified sample size. Results: From the acute stroke patients, found HDL levels 33.97 mg / dl, recurrent stroke patients found HDL levels 35.25 mg/dl. LDL levels in acute stroke patients were 109.56 mg/dl and recurrent stroke patients were 123.16 mg/dl. Mann-Whitney statistical test results obtained p value for comparison of HDL levels of 0.851 and p value on t test for comparison of LDL levels of 0.497. Conclusion: There was no difference in mean HDL and LDL levels from acute ischemic stroke patients and recurrent stroke.Keywords: atherocsclerosis, cerebrovascular disease, HDL, LDL, stroke